Association of dietary preferences with primary ovarian insufficiency (POI): a mendelian randomization-based analysis - Zhengqi Qiu; Emma Yun Zhi Huang; Yufei Li; Jun Du; Juntao Kan (BMC Women's Health)
Abstract Background Primary ovarian insufficiency (POI) is a critical cause of infertility and is increasingly recognized as a complex metabolic disorder. Dietary factors may influence the risk of POI, but causal relationships remain unclear. Methods We conducted an MR study using genetic instrumental variables for 83 dietary preferences from the UK Biobank, with the Inverse Variance Weighted method as the primary analysis. Results Consumption of butter and full-fat dairy products was strongly associated with an increased risk of primary ovarian insufficiency (POI). Women who consumed butter had nearly ten times the risk of developing POI (OR = 9.54, p = 0.048), while full-cream milk was associated with an even greater risk (OR = 29.22, p = 0.018). Interestingly, semi-skimmed milk, despite its lower fat content, also showed a significant positive association with POI (OR > 100, p = 0.008). In contrast, dietary patterns including oily fish and pork were protective against POI. Oily fish, rich in omega-3 fatty acids, was linked to a 82% reduced risk of POI (OR = 0.18, p = 0.008), and pork consumption also showed a protective effect (OR = 0.13, p = 0.041). Additionally, women who did not consume eggs had a significantly lower risk of POI (OR < 0.001, p = 0.044). Conclusion This study demonstrates that high-fat dairy products may increase the risk of POI, while oily fish and pork consumption could offer protective effects. These findings providing a foundation for future clinical and public health strategies targeting reproductive health.